Generation of a Polyclonal Antibody against the Mouse Metal Transporter ZIP8 - Guojun Wei; Yuze Wu; Ningning Zhao (Antibodies, 2021)
ZIP8 is a newly identified metal transporter. In human patients, mutations in ZIP8 result in severe manganese deficiency, suggesting a critical role for ZIP8 in regulating systemic manganese homeostasis. In mice, the deletion of ZIP8 recapitulates the symptoms of patients with ZIP8 mutations. However, further studies using mouse models to examine ZIP8′s function were hindered by the lack of suitable antibodies to detect endogenous ZIP8 protein. In this study, we report the design, generation, and validation of a polyclonal antibody against mouse ZIP8. We have demonstrated that the newly generated antibody can be reliably used in immunoblotting analysis to detect endogenous ZIP8 protein in mouse tissues. The successful generation and validation of anti-mouse ZIP8 antibody provide opportunities to further examine the function and regulation of this metal transporter. In addition, our study may provide valuable insights into the future development of antibodies targeting polytopic membrane proteins.